Prophylaxis and management of skin toxicities - Salzmann, Martin; Marmé, Frederik; Hassel, Jessica C. (Breast care, 2019)
Skin toxicity is a common problem not only when treating breast cancer but in all cancer types. Visible on the surface, these side effects come not just with burdening symptoms but also with stigmatization. With increasing diversity in therapeutic options, dermatologic side effects are also becoming increasingly complex and more challenging for the clinician. We reviewed the most common dermatologic side effects of current anticancer therapy, including toxicity induced by chemotherapy, targeted therapy, and immunotherapy. In particular, we focus on xerosis and pruritus, (acneiform) exanthema, hand-foot syndrome, nail toxicities, alopecia, and mucositis. We propose measures for the prevention and management of these side effects based on current literature. With high incidences in both chemotherapy and targeted therapy, prophylactic measures are crucial to reducing the incidence and severity of skin toxicity and therefore key to therapy adherence. Appropriate management of these toxicities will help avoid unnecessary treatment discontinuation.